Identification and characterization of enhancers controlling the inflammatory gene expression program in macrophages - Ghisletti, Serena; Barozzi, Iros; Mietton, Flore; Polletti, Sara; De Santa, Francesca; Venturini, Elisa; Gregory, Lorna; Lonie, Lorne; Chew, Adeline; Wei, Chia-Lin; Ragoussis, Jiannis; Natoli, Gioacchino (Immunity (Cambridge, Mass.), 2010)
Enhancers determine tissue-specific gene expression programs. Enhancers are marked by high histone H3 lysine 4 mono-methylation (H3K4me1) and by the acetyl-transferase p300, which has allowed genome-wide enhancer identification. However, the regulatory principles by which subsets of enhancers become active in specific developmental and/or environmental contexts are unknown. We exploited inducible p300 binding to chromatin to identify, and then mechanistically dissect, enhancers controlling endotoxin-stimulated gene expression in macrophages. In these enhancers, binding sites for the lineage-restricted and constitutive Ets protein PU.1 coexisted with those for ubiquitous stress-inducible transcription factors such as NF-kappaB, IRF, and AP-1. PU.1 was required for maintaining H3K4me1 at macrophage-specific enhancers. Reciprocally, ectopic expression of PU.1 reactivated these enhancers in fibroblasts. Thus, the combinatorial assembly of tissue- and signal-specific transcription factors determines the activity of a distinct group of enhancers. We suggest that this may represent a general paradigm in tissue-restricted and stimulus-responsive gene regulation.